2020
DOI: 10.31197/atnaa.786151
|View full text |Cite
|
Sign up to set email alerts
|

The rise and fall of L-spaces

Abstract: For a quite long period, the so-called L-structure or L-spaces have been studied by some authors. They have several trivial misconceptions such as their L-spaces extend the well-known generalized convex (G-convex) spaces. In order to clarify this matter and others, we show that our KKM theory on abstract convex spaces improves typical results in L-spaces. Main topics in this paper are related to extensions of the Himmelberg fixed point theorem. Since such studies are beyond of L-spaces, we cordially claim that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…In our previous work [34] in 2013, we showed that better forms of theorems in [5,7,8,9,11] can be deduced from a KKM theorem on abstract convex spaces in our sense [2327]. Moreover, in our recent work [38], we showed that our KKM theory on abstract convex spaces improves and extends all of typical results on L-spaces. Since such studies are beyond of L-spaces, we cordially claimed that now is the proper time to…”
Section: Introductionsupporting
confidence: 54%
“…In our previous work [34] in 2013, we showed that better forms of theorems in [5,7,8,9,11] can be deduced from a KKM theorem on abstract convex spaces in our sense [2327]. Moreover, in our recent work [38], we showed that our KKM theory on abstract convex spaces improves and extends all of typical results on L-spaces. Since such studies are beyond of L-spaces, we cordially claimed that now is the proper time to…”
Section: Introductionsupporting
confidence: 54%
“…The present article is a continuation of our previous works [34], [35] on the rise and fall of the L-spaces due to Ben-El-Mechaiekh, Chebbi, Florenzano, and Llinares [1] in 1998. Since then there have appeared some people concentrating mainly on L-spaces and they can be adequately called L-space theorists.…”
Section: Introductionmentioning
confidence: 54%
“…In [34], we showed that our KKM theory on abstract convex spaces improved typical results on L-spaces. Main topics there were related to extensions of the Himmelberg fixed point theorem.…”
Section: Introductionmentioning
confidence: 68%
See 2 more Smart Citations